Role of CT Nose Paranasal Sinuses and Nasal Endoscopy for Decision Making in a Case of Deviated Nasal Septum - Sayan Hazra; Ankit Choudhary; Swapan Kumar Ghosh; Subhradev biswas; Kaustuv Das Biswas (Bengal Journal of Otolaryngology and Head Neck Surgery, 2019)
Introduction